2008
DOI: 10.1016/j.parkreldis.2007.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Rotating treadmill training reduces freezing in Parkinson disease: Preliminary observations

Abstract: Two subjects with Parkinson disease (PD) who had difficulty turning, and freezing of gait triggered by turning, participated. Subjects completed four blocks of turning trials. Three blocks were conducted in the absence of treadmill intervention. Both subjects had consistent freezing across blocks prior to training and evidenced more freezing when turning left than right. The final block of turns was performed after 10-15 minutes of training leftward turning on a rotating circular treadmill. Following training:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 11 publications
(14 reference statements)
0
20
0
Order By: Relevance
“…24 It has been proposed that freezing results from a combination of hypokinesia (steps are smaller than normal at the outset of walking) and the sequence effect (steps become progressively smaller over the course of a walking trial). 25 In this line, Danoudis et al 26 observed that PD patients with FOG had smaller step lengths than PD patients without FOG in different walking conditions and suggested that step length was directly linked to decreased coordination of gait (another potential reason behind FOG). Therefore, interventions aimed at enhancing baseline step length could contribute to a reduction in freezing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 It has been proposed that freezing results from a combination of hypokinesia (steps are smaller than normal at the outset of walking) and the sequence effect (steps become progressively smaller over the course of a walking trial). 25 In this line, Danoudis et al 26 observed that PD patients with FOG had smaller step lengths than PD patients without FOG in different walking conditions and suggested that step length was directly linked to decreased coordination of gait (another potential reason behind FOG). Therefore, interventions aimed at enhancing baseline step length could contribute to a reduction in freezing.…”
Section: Discussionmentioning
confidence: 99%
“…28 Another possible mechanism for freezing is diffi culty executing well-learned motor skills, such as walking and turning. 25 This impaired performance is due to a disorder in sensory-motor integration resulting from a dopaminergic basal ganglia and executive dysfunction. 30 In this regard, it has been suggested that external sensory cues could be effective in overcoming the defective basal ganglia circuitry of PD patients, perhaps by activating the motor cortex via alternative circuitries.…”
Section: Discussionmentioning
confidence: 99%
“…23 The rotating treadmill has become a new therapeutic tool to improve freezing symptoms during turning. 9 The stride length and swing velocity of the outer leg (further from the center of curvature) should be greater than the inner leg when walking along curved trajectories. 24 The kinematic and dynamic constraints, amplitude, and firing timings of muscle activation are more adapted in rotating locomotion than in normal straight walking.…”
Section: Rehabilitation In Pdmentioning
confidence: 99%
“…8 These symptoms all decrease mobility, and, subsequently, may lead to falls. 9 Some patients with PD also have speech problems. Studies revealed that patients with PD have lower functional abilities and strength in comparison with healthy individuals.…”
Section: Rehabilitation In Pdmentioning
confidence: 99%
See 1 more Smart Citation